Faktor-Faktor yang Berhubungan dengan Siklus Menstruasi pada Wanita Usia Subur: Literature Review - Dhiya Ulhaq, Ghina; Wittiarika, Ivon Diah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Menstruation is associated with sexual maturity, fertility, overall health, and even changes in various parts of the body. The menstrual cycle typically remains relatively stable during the reproductive years. However, 11.7% of adolescent girls in Indonesia experience menstrual cycle disturbances. Therefore, it is essential to identify factors related to the menstrual cycle. The study was a literature review. The literature used consisted of articles from national journals published in the last five years (2018–2023). The literature sources were obtained from